ผลของพืชสวนบำบัดร่วมกับกลุ่มจิตวิทยาพัฒนาตนและการปรึกษาเชิงจิตวิทยาแนวพุทธ ที่มีต่อปัญญา และความเป็นเนื้อเดียวกันกับธรรมชาติ ของนิสิตนักศึกษามหาวิทยาลัย - อติชาต ตันติโสภณวนิช (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This study aimed to examine the effect of therapeutic horticulture program with Buddhist Personal Growth and Counseling Group on PAÑÑĀ and connectedness to nature of undergraduates through the quasi-experimental with pretest-posttest control group design. Participants were 61 undergraduates (18 males and 43 females). They were randomly assigned to two experimental groups and one control group (n = 5 - 9 per group). Participants in experimental groups participated in the group 24 hours in total (3 hours per week for 8 consecutive weeks). Instruments were PAÑÑĀ in Interconnectedness and Change Scale and Connectedness to Nature Scale. Two-way mixed-design multivariate analysis of variance was used for data analysis. Findings reveal: 1. The posttest scores on PAÑÑĀ of the therapeutic horticulture program with Buddhist personal growth and counseling group were significantly higher than the scores of the therapeutic horticulture group (p < .01) and the scores of the control group (p < .001) 2. No significant difference was found between the posttest scores on PAÑÑĀ of the therapeutic horticulture group and the control group. 3. The posttest scores on connectedness to nature of the therapeutic horticulture program with Buddhist personal growth and counseling group were significantly higher than the scores of the control group (p < .001). No significant difference was found between the posttest scores on connectedness to nature of the therapeutic horticulture program with Buddhist personal growth and counseling group and the therapeutic horticulture group. 4. No significant difference was found between the posttest scores on PAÑÑĀ of the therapeutic horticulture group and the control group.